Critical Influenza-Like Illness in a Nine-Year-Old Associated With a Poultry-Origin H9N2 Avian Influenza Virus: Risk Assessment and Zoonotic Potential - Zhao, Fengming; Wang, Yuqing; Chen, Liping; Zhang, Xinxing; Ducatez, Mariette; He, Jiayang; Wan, Zhimin; Ye, Jianqiang; Bai, Zhenjiang; Xia, Yu; Dong, Zefeng; Gu, Wenjing; et al. (Frontiers in Virology, 2021)
Subtype H9N2 avian influenza viruses (AIV), now the predominant avian influenza virus subtype in poultry in China, cause sporadic human infections manifesting as mild influenza-like illness. We isolated an H9N2 AIV from a critical case of respiratory illness in a 9-year-old with no underlying conditions. As this virus was associated with critical illness, we conducted a risk assessment to determine its mammalian pathogenicity. Clinical and laboratory data were collected from hospital records. A/Suzhou/GIRD01/2019 (H9N2) (GIRD01) was isolated from a throat swab and used in risk-assessment studies in comparison to prototypical and contemporary H9N2 AIVs and contemporary seasonal subtype H1N1 and H3N2 influenza viruses. The patient presented with fever, vomiting but rapidly declined to progressive wheezing followed by dyspnea. The patient was admitted to the intensive care unit and placed on mechanical ventilation. A diagnosis of pneumonia and type I respiratory failure was made. Viral RNA was detected in the bronchiolavelolar lavage and anal swab specimens, suggesting lower lung and extrapulmonary involvement. Respiratory syncytial virus was also detected by immunofluorescence in bronchiolavelolar lavage. Following an aggressive regimen of antiviral and antibacterial therapy, the patient recovered and was discharged from hospital after 13 days. GIRD01 was closely related to poultry-origin H9N2 AIVs in the area and contained several known markers of mammalian pathogenicity. GIRD01 also showed a strong affinity for mammalian-type over avian-type sialic acids. GIRD01 replicated more efficiently compared to older H9N2 viruses and contemporary seasonal viruses in vitro and produced asymptomatic infections in mice. In summary, GIRD01 was well-adapted to replication in in vitro and in vivo mammalian models but was not more pathogenic compared to similar contemporary strains of H9N2 AIVs. Therefore, these viruses may pose a risk of causing severe respiratory disease in humans.